Prevalência de transtornos mentais em população indígena infantil da floresta amazônica - Taveira, Daniela Londe Ribeiro (2018)
Objective: To determine the prevalence of mental disorders in children and adolescents of an indigenous village population in the Brazilian Amazon. Methods: Analytical prevalence study in a sample of 214 Karajá indigenous children and adolescents, aged between 07 and 14 years. Prevalences were determined by the Strength and Difficulties Questionnaire (SDQ), in their SDQ- Por versions P4-17 and SDQ-Por T4-17, respectively for parents/caregivers and teachers of young people between 4 and 17 years of age. The difference between the prevalences found by the evaluators (teachers and parents) and the risk association between sex, age and psychiatric symptoms were evaluated. Results: A prevalence of total problems of 22.1% according to the SDQ-Por Pa4-17 and 15.2% according to the SDQ-Por T4-17 was found, and a weak agreement index among the reviewers was found for the total prevalence of problems (k = 0.042, P = 0.007). There was a greater occurrence of psychiatric symptoms and psychiatric disorders in children (7 to 10 years) than in adolescents (11 to 14 years). Conclusion: The prevalence of the total score of difficulties is higher than that found in national and international studies with non-indigenous population, but similar to the rates with indigenous population. It was observed that even in the Karajá ethnic group, which preserves the primordial cultural aspects of their ancestors that lived 10,000 years ago, there are psychiatric problems with clinical presentations similar to those found in modern civilized societies, and the cultural context may influence the manifestations of symptoms and prevalence.